2020
DOI: 10.1002/sia.6854
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis of bacterial systems using cryo‐X‐ray photoelectron spectroscopy

Abstract: Surface analysis of biological systems using XPS often requires dehydration of the sample for it to be compatible with the ultrahigh vacuum of the spectrometer. However, if samples are frozen to liquid-nitrogen temperature prior to and during analysis, water can be retained in the sample and the organization of the sample surface should be preserved to a higher degree than in desiccated samples. This article presents recent developments of cryo-X-ray photoelectron spectroscopy (cryo-XPS) for analyses of hydrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In order to predict the contribution of peptides (proteins and peptidoglycans), lipids and polysaccharides in the C 1s spectra of the nine samples, "the Umeå method" was employed. It predicted that 66±4% of detected surface C atoms originated from proteins or peptidoglycans, 8±2% from lipids and 26±2 from polysaccharides (Supplementary Table S4), in line with what has previously been reported for bacterial cells (Hagberg et al, 2020;Ramstedt et al, 2011;Ramstedt et al, 2014).…”
Section: Cryo-xpssupporting
confidence: 88%
See 4 more Smart Citations
“…In order to predict the contribution of peptides (proteins and peptidoglycans), lipids and polysaccharides in the C 1s spectra of the nine samples, "the Umeå method" was employed. It predicted that 66±4% of detected surface C atoms originated from proteins or peptidoglycans, 8±2% from lipids and 26±2 from polysaccharides (Supplementary Table S4), in line with what has previously been reported for bacterial cells (Hagberg et al, 2020;Ramstedt et al, 2011;Ramstedt et al, 2014).…”
Section: Cryo-xpssupporting
confidence: 88%
“…Alternatively, the bacterial cells were washed with PBS (containing 8 g L −1 NaCl, 0.2 g L −1 KCl, 1.44 g L −1 Na 2 HPO 4 , 0.24 g L −1 KH 2 PO 4 at pH 7.4), centrifuged, the supernatant discarded, and approximately 20 µL of the pellet was transferred using an automatic pipette to the sample holder forming a dense droplet (this wash was performed only for some of the replica of cryo-XPS, and not for NAP-XPS). Thereafter, the bacterial biomass was fast-frozen in the sample introduction chamber under a gentle flow of dry nitrogen, the pressure reduced, the sample transferred into the analysis chamber, and analyzed by cryo-XPS in accordance with previously described procedures ( Ramstedt and Shchukarev, 2016 ; Hagberg et al, 2020 ). Previous studies have shown no significant differences in major peaks (C1s and N1s) between washed and non-washed P. fluorescens bacteria grown on LB agar culture plates ( Hagberg et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations